Design and implementation of quadratic boost converter employing arduino microcontroller - Kurnia Deca Nevil, Prayoga; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2024)
In modern power conversion applications, efficiency and the ability to significantly boost the voltage are two important aspects to consider. This article discusses the design and analysis of the Quadratic Boost Converter (QBC), a power converter that offers a higher voltage boost ratio compared to conventional boost converters. The Quadratic Boost Converter uses two inductors and two capacitors arranged in such a way as to boost the input voltage to a higher level with better efficiency. This study includes simulations and laboratory experiments to measure the performance of the Quadratic Boost Converter under various load and input voltage conditions. The results show that the Quadratic Boost Converter is not only able to achieve a higher voltage boost ratio but also has better efficiency under various operating conditions. This study also highlights the advantages of the Quadratic Boost Converter in solar power systems and electric vehicle applications, where significant voltage boost and high efficiency are highly required. Thus, the Quadratic Boost Converter is a potential solution for the need for more efficient and effective power conversion in various modern electronic applications